2010
DOI: 10.1021/ja105510k
|View full text |Cite
|
Sign up to set email alerts
|

Supermolecular-Chromophore-Sensitized Near-Infrared-to-Visible Photon Upconversion

Abstract: Selective near-IR (NIR) excitation (780 nm) of the conjugated supermolecule ruthenium(II) [15-(4'-ethynyl-(2,2';6',2''-terpyridinyl))-bis[(5,5',-10,20-di(2',6'-bis(3,3-dimethylbutoxy)phenyl)porphinato)zinc(II)]ethyne][4'-pyrrolidin-1-yl-2,2';6',2''-terpyridine] bis(hexafluorophosphate) (Pyr(1)RuPZn(2)) in solutions containing N,N-bis(ethylpropyl)perylene-3,4,9,10-tetracarboxylicdiimide (PDI) or tetracene gives rise to a substantial anti-Stokes energy gain (PDI, 0.70 eV; tetracene, 0.86 eV). Experimental data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
139
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 73 publications
4
139
0
Order By: Relevance
“…
Molecular nonlinear-optical (NLO) phenomena are currently being exploited for the design of visible emitting bioprobes with unprecedented properties that result from 1) the transparency of living tissues toward low-energy near-infrared (NIR) incident radiation and 2) the improved focusing of the light from an excitation laser beam within nanometric volumes.[1] Nonresonant multiphoton absorption produces a single emission during the irradiation; this emission corresponds to a multiple of the energy of the incident beam, as, for example, in second-harmonic generation (Figure 1 a), while resonant multiphoton absorption populates a real excited state of the chromophore, which relaxes and fluoresces with the same characteristics as if sensitized by a linear excitation process (Figure 1 b).[2] Beyond the optimization of polarizable push-pull p-aromatic molecules for NLO optical response, [2] and the related development of upconverted fluorescence signals in polyaromatic platforms produced by metal-sensitized triplet-triplet annihilation photochemistry, [3] Le Bozec, Maury, Andraud, and their respective co-workers demonstrated that trivalent lanthanide ions (Ln III ) may efficiently contribute to the polarization of coordinated aromatic ligands for resonant multiphoton absorption.[4] Moreover, the wealth of accessible long-lived metal-centered luminescent emissive levels can be exploited for two-photon-excited time-gated fluorescence analyses of biological tissues. [5] Interestingly, the existence of several real excited states located between the ground state and the target excited state of lanthanide acceptors opens novel perspectives for the operation of alternative sensitizing mechanisms that take advantage of these electronic relays for successive linear excitations by one (Figure 1 c) or several (Figure 1 d) moieties, thus leading to an excited-state absorption (ESA) process or sequential energy transfer upconversion (ETU), both of which are followed by luminescence.

[6] Although they operate by different principles, that is, they involve real rather than virtual intermediate excited levels during the multiphoton absorption processes, two-photon upconversion fluorescence processes (Figure 1 c, d) can be considered as nonlinear because of the quadratic dependence of the efficiency (I) on the incident intensity of the excitation light (I / P 2 ).

…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…
Molecular nonlinear-optical (NLO) phenomena are currently being exploited for the design of visible emitting bioprobes with unprecedented properties that result from 1) the transparency of living tissues toward low-energy near-infrared (NIR) incident radiation and 2) the improved focusing of the light from an excitation laser beam within nanometric volumes.[1] Nonresonant multiphoton absorption produces a single emission during the irradiation; this emission corresponds to a multiple of the energy of the incident beam, as, for example, in second-harmonic generation (Figure 1 a), while resonant multiphoton absorption populates a real excited state of the chromophore, which relaxes and fluoresces with the same characteristics as if sensitized by a linear excitation process (Figure 1 b).[2] Beyond the optimization of polarizable push-pull p-aromatic molecules for NLO optical response, [2] and the related development of upconverted fluorescence signals in polyaromatic platforms produced by metal-sensitized triplet-triplet annihilation photochemistry, [3] Le Bozec, Maury, Andraud, and their respective co-workers demonstrated that trivalent lanthanide ions (Ln III ) may efficiently contribute to the polarization of coordinated aromatic ligands for resonant multiphoton absorption.[4] Moreover, the wealth of accessible long-lived metal-centered luminescent emissive levels can be exploited for two-photon-excited time-gated fluorescence analyses of biological tissues. [5] Interestingly, the existence of several real excited states located between the ground state and the target excited state of lanthanide acceptors opens novel perspectives for the operation of alternative sensitizing mechanisms that take advantage of these electronic relays for successive linear excitations by one (Figure 1 c) or several (Figure 1 d) moieties, thus leading to an excited-state absorption (ESA) process or sequential energy transfer upconversion (ETU), both of which are followed by luminescence.

[6] Although they operate by different principles, that is, they involve real rather than virtual intermediate excited levels during the multiphoton absorption processes, two-photon upconversion fluorescence processes (Figure 1 c, d) can be considered as nonlinear because of the quadratic dependence of the efficiency (I) on the incident intensity of the excitation light (I / P 2 ).

…”
mentioning
confidence: 99%
“…[2] Beyond the optimization of polarizable push-pull p-aromatic molecules for NLO optical response, [2] and the related development of upconverted fluorescence signals in polyaromatic platforms produced by metal-sensitized triplet-triplet annihilation photochemistry, [3] Le Bozec, Maury, Andraud, and their respective co-workers demonstrated that trivalent lanthanide ions (Ln III ) may efficiently contribute to the polarization of coordinated aromatic ligands for resonant multiphoton absorption.…”
mentioning
confidence: 99%
See 3 more Smart Citations